Incidence of urinary tract infection in surgical patients after short term catheterization in a tertiary care institute - Bagree, Rajendra; Srinivas, Vinay; Kumar, Ritesh; Gupta, Ayush; Kumar, Naveen; Kumar, Nitish (International Surgery Journal, 2024)
Background: We aim to assess the rate of catheter associated urinary tract infection in patients undergoing catheterization in our surgical ward. Urinary catheters pose a potential risk of introducing infections in the urinary system. We observed the setting of catheterization and incidence of UTIs, prevalence, contributing factors, and potential preventive measures. We aim to enhance the quality of patient care and reduce the burden of post-catheterization complications. Methods: The research methodology involves a retrospective analysis of patient records, encompassing a large sample size from the tertiary care institute. Data collection includes patient demographics, duration of catheterization, underlying health conditions, and microbial profiles. Statistical analyses will be employed to discern patterns, risk factors, and correlations. Results: 322 patients admitted in our surgical ward were catheterized as a part of this study, out of which 170 patients came under the inclusion criteria, including 63 males and 107 females. It was found that 19 patients, 13 female and 6 males, had developed positive urine cultures on day 3 of catheterization, with 6 patients showing symptoms of UTI. 14 out of 19 cultures were positive for E. coli, 3 for Klebsiella sp., 1 for Citrobacter spp. And 1 for E. gallinarum. Conclusions: In this study, we concluded that maximum cases of CAUTI were due to inappropriate catheterization in emergency surgical procedures, where proper aseptic standards were not applied. Preventive strategies should be applied to minimize the incidence and complications of CAUTI.